Yarn degradation during weaving process and its effect on the mechanical behaviours of 3D warp interlock p-aramid fabric for industrial applications. Issue 5 (June 2022) - Abtew, Mulat Alubel; Boussu, François; Bruniaux, Pascal; Loghin, Carmen; Cristian, Irina; Chen, Yan; Wang, Lichuan
Three dimensional (3D) warp interlock fabric becomes a promising structure due to its good mechanical performances. However, its complex manufacturing process can cause severe yarn damage and affects its overall final performances. The current study addressed the effects weaving process and warp yarn ratios on the multi-filaments yarn degradations and its mechanical performances while 3D warp interlock fabric manufacturing. Four different 3D warp interlock variants having similar fabric architecture, and yarn densities but different warp yarns interchange ratios were manufactured using 930dTex high-performance multi-filament (Twaron® f1000). The multi-filaments yarns at different weaving processes were tested for their tensile properties. The results show that the average tensile strength of twisted yarns show a decrement of 5.68% as compared to the bobbin yarns. Meanwhile, warping process also showed a 16.11% maximum breaking load reduction as compared to the bobbin yarn. Besides, the tensile strength of binding yarn after weaving process for samples 3D-8/0, 3D-8/4, and 3D-8/8 was reduced by 12.79%, 5.22%, and 14.22% respectively as compared to the yarn after warping process. In conclusion, yarn degradation inside the 3D woven structure was affected not only by the various process parameters but also by the type of fabric architecture made with different warp yarn ratios. These phenomena ultimately bring a great influence both on the yarn and overall mechanical performance of the final products. For this, further studies are planned to investigate the multi-filaments yarn degradation effect on the ballistic performances fibrous material as it is directly linked to the yarn performance.